2019
DOI: 10.32604/cmes.2019.04828
|View full text |Cite
|
Sign up to set email alerts
|

An IB Method for Non-Newtonian-Fluid Flexible-Structure Interactions in Three-Dimensions

Abstract: Problems involving fluid flexible-structure interactions (FFSI) are ubiquitous in engineering and sciences. Peskin's immersed boundary (IB) method is the first framework for modeling and simulation of such problems. This paper addresses a three-dimensional extension of the IB framework for non-Newtonian fluids which include power-law fluid, Oldroyd-B fluid, and FENE-P fluid. The motion of the non-Newtonian fluids are modelled by the lattice Boltzmann equations (D3Q19 model). The differential constitutive equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Numerical results of flows around an impulsively started circular cylinder were presented in the contribution confirmed the efficiency, for Reynolds numbers 1000 and 3000 [Bouchon, Dubois and James (2019)]. An extension of the IB framework for FSI problems was proposed for non-Newtonian fluids with power-law, Oldroyd-B, and FENE-P fluids in three dimensions in the manuscript [Zhu (2019)]. The motions of the non-Newtonian fluids were modelled in the contribution with the lattice Boltzmann equations (D3Q19 model) [Zhu (2019)].…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Numerical results of flows around an impulsively started circular cylinder were presented in the contribution confirmed the efficiency, for Reynolds numbers 1000 and 3000 [Bouchon, Dubois and James (2019)]. An extension of the IB framework for FSI problems was proposed for non-Newtonian fluids with power-law, Oldroyd-B, and FENE-P fluids in three dimensions in the manuscript [Zhu (2019)]. The motions of the non-Newtonian fluids were modelled in the contribution with the lattice Boltzmann equations (D3Q19 model) [Zhu (2019)].…”
mentioning
confidence: 70%
“…An extension of the IB framework for FSI problems was proposed for non-Newtonian fluids with power-law, Oldroyd-B, and FENE-P fluids in three dimensions in the manuscript [Zhu (2019)]. The motions of the non-Newtonian fluids were modelled in the contribution with the lattice Boltzmann equations (D3Q19 model) [Zhu (2019)]. The multi-scale hybrid-mixed (MHM) method was applied to the numerical approximation of two-dimensional matrix fluid flow in porous media with fractures in the manuscript [Zhang (2019)].…”
mentioning
confidence: 99%
“…Here, the lattice Boltzmann method is utilized to solve the Navier-Stokes equations and the constitutive equations of the viscoelastic model [18,19,16,15,17]. It should be noted that a diffusion parameter κ is normally involved in this method (in the transport equations of the conformation tensor C) to improve the stability of simulations, and more details can be found in Refs.…”
Section: Mathematical Model and Numerical Methodsmentioning
confidence: 99%
“…In addition, the accuracy of this method was confirmed by different validation cases (2D Oldroyd-B flow over a cylinder, a 3D spherical particle rotation in an Oldroyd-B shear flow, and a 3D spherical particle sedimentation in Newtonian fluid under gravity). More recently, LBM and IBM were combined to study the motion of a massless flexible sheet in viscoelastic flows by Zhu [15,17], where the LBM originally proposed by Malaspinas et al [18] was utilized to solve the viscoelastic flow, and the FSI was enforced by IBM. In this study, it was reported that the motion of the sheet may be hindered with the inclusion of the fluid viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Although that FSI has been a major research topic in the past decades, approaches specifically targeting generalised Newtonian fluid flow are still scarcely found in literature [87,[95][96][97][98], even more so, when putting emphasis on efficient coupling schemes and solution procedures. The fluid flow problem, especially if treated semi-implicitly, has to be handled with special care.…”
Section: Introductionmentioning
confidence: 99%